Measuring Food Literacy : The Survelliance of Elderly Teachers and Education Staffs’ Food Literacy Level (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2023)
The “food literacy” is increasingly used to describe knowledge, skills and behaviors needed to meet food needs. The aim of this survey research was to measure food literacy level among elderly teachers and education staffs. Methods: This surveillance using FLQ-EE(Food Literacy Questionnaires of Elderly teachers and Education staffs) which created by authors. The participants were 170 elderly teachers and education staffs selected by census population in Bangkok Province Centre of the Welfare Promotion Commission for Elderly teacher and Educational staffs which was overweight (BMI≥23.0). The data were analysed by percentage, average and standard deviation. Results: The participants were interactive level in food knowledge and nutrition. Food skills including Food selecting, Food planning and manage, Food preparing were functional level. Excepted Eating was Critical level. Conclusions: Mostly,food literacy level surveillance indicates that it's on a satisfactory level. Therefore, appropriate learning should be promoted further.